1969
DOI: 10.1152/jappl.1969.26.5.540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of altitude acclimatization on blood composition of women

Abstract: The effects of altitude acclimatization on blood composition were studied in eight University of Missouri (elev 700 ft) coeds who lived on the summit of Pikes Peak (elev 14,000 ft) for 10 weeks. During the period of altitude exposure the following changes were observed: a transient increase in heart rate, the maximum being reached on 1st day of exposure; an early rapid increase in hematocrit and hemoglobin which later became more gradual; an early and sustained reduction in plasma volume; a rapid initial incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…This period also allowed additional time to restore bone marrow iron stores in those athletes who were iron deficient. Previous work by the authors (Stray-Gundersen et al, 1993 and others (Hannon et al, 1969) demonstrated that individuals who are iron deficient are unable to increase the red cell mass in response to altitude exposure; (3) athletes were then randomized into one of three training groups (n 5 13 for each; 9 men, 4 women), where they were exposed for 4 weeks to (a) the primary experimental group, where the athletes lived at 2500 m and traveled down to a lower altitude of 1250 m once or twice per day to train (high-low); (b) an altitude control (high-high), where the athletes lived at 2500 m together with the hi-lo athletes, but did all their training at the same altitude or higher (2500-3000 m); and (c) a sealevel control, where the athletes traveled to a new training camp environment with mountainous terrain, but at sea-level altitude (low-low). The volume and relative intensity of training were closely matched among groups and followed the same pattern as the previous 4 weeks of training at sea level.…”
Section: The Living High-training Low Modelmentioning
confidence: 95%
“…This period also allowed additional time to restore bone marrow iron stores in those athletes who were iron deficient. Previous work by the authors (Stray-Gundersen et al, 1993 and others (Hannon et al, 1969) demonstrated that individuals who are iron deficient are unable to increase the red cell mass in response to altitude exposure; (3) athletes were then randomized into one of three training groups (n 5 13 for each; 9 men, 4 women), where they were exposed for 4 weeks to (a) the primary experimental group, where the athletes lived at 2500 m and traveled down to a lower altitude of 1250 m once or twice per day to train (high-low); (b) an altitude control (high-high), where the athletes lived at 2500 m together with the hi-lo athletes, but did all their training at the same altitude or higher (2500-3000 m); and (c) a sealevel control, where the athletes traveled to a new training camp environment with mountainous terrain, but at sea-level altitude (low-low). The volume and relative intensity of training were closely matched among groups and followed the same pattern as the previous 4 weeks of training at sea level.…”
Section: The Living High-training Low Modelmentioning
confidence: 95%
“…A similar mechanism to increase arterial oxygen content is seen when humans are exposed to high altitude. Here haemoglobin concentration and the arterial oxygen content are increased by a fall in plasma volume within the first day of exposure, and after approximately 12 days an increase in red blood cell mass also contributes to the normalisation of haemoglobin concentration (Hannon et al . 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Here haemoglobin concentration and the arterial oxygen content are increased by a fall in plasma volume within the first day of exposure, and after approximately 12 days an increase in red blood cell mass also contributes to the normalisation of haemoglobin concentration (Hannon et al 1969). It appears beneficial that plasma volume is decreased in the acute presence of hypoxia since such a response increases oxygenation rapidly as compared with a mechanism depending exclusively on augmented erythropoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…[15,17,31]). Astonishingly nearly all measurements of the latter quantities were done in males until now, in few cases data of both sexes were pooled.…”
mentioning
confidence: 99%